Sosialisasi Kesehatan Bagi Para Lansia Untuk Meningkatkan Kualitas Hidup - Linda Puspitasari; Aji Primanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This service aims to provide socialization on the importance of health for older people to improve their quality of life. The method used in this service is descriptive quantitative with surveys, observations, and documentation. The subjects of this research were older adults located in Plamongan Hijau Housing, Pedurungan Kidul Village, Pedurungan District, Semarang City, with 20 elderly participants. The service results show that older people's knowledge about the health of the elderly has increased. Older people realize the importance of maintaining health through sports activities and a healthy lifestyle.